ANALYSIS OF MODE CHOICE BEHAVIOR USING RUM AND RRM - Surbakti, Medis Sejahtera; Sadullah, A. Farhan Mohd.; Yahya, Ahmad Shukri (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
A mode choice on transportation model, are developed based on the economic theory is called the Random Utility Maximization (RUM), which emphasizes the use of rationality in the selection process. In 2008, Caspar G. Chorus developed the Random Regret Minimization (RRM) theory, which facilitated the development of the voting behavior theory (choice behavior), in which a state of choice behavior minimizes regret that may arise from selection. This preliminary study aims to demonstrate differences in the calculation results in the analysis of RUM and RRM in the case of the selection of vehicle types. Such results exhibit the intermodal characteristic of work or business travel. The method of analysis used in this study is the stated preference technique. Results of the comparison analysis between RUM and RRM showed no significant difference across the purposes of travel, total travel time, and destination point.